Identification of community-dwelling older adults at risk of frailty using the PERSSILAA screening pathway: a methodological guide and results of a large-scale deployment in the Netherlands - Stephanie Jansen-Kosterink; Lex van Velsen; Sanne Frazer; Marit Dekker-van Weering; Rónán O'Caoimh; Miriam Vollenbroek-Hutten (BMC, 2019)
Abstract Background Among community-dwelling older adults, frailty is highly prevalent and recognized as a major public health concern. To prevent frailty it is important to identify those at risk of becoming frail, but at present, no accepted screening procedure is available. Methods The screening process developed as part of the PERSSILAA project is a two-step screening pathway. First, older adults are asked to complete a self-screening questionnaire to assess their general health status and their level of decline on physical, cognitive and nutritional domains. Second, older adults who, according to step one, are at risk of becoming frail, are invited for a face-to-face assessment focusing on the domains in depth. We deployed the PERSSILAA screening procedure in primary care in the Netherlands. Results In total, baseline data were available for 3777 community-dwelling older adults (mean age 69.9 (SD ± 3.8)) who completed first step screening. Based on predefined cut-off scores, 16.8% of the sample were classified as frail (n = 634), 20.6% as pre-frail (n = 777), and 62.3% as robust (n = 2353). Frail subjects were referred back to their GP without going through the second step. Of the pre-frail older adults, 69.7% had evidence of functional decline on the physical domain, 67% were overweight or obese and 31.0% had evidence of cognitive decline. Conclusion Pre-frailty is common among community-dwelling older adults. The PERSSILAA screening approach is a multi-factor, two-step screening process, potentially useful for primary prevention to identify those at risk of frailty and who will benefit most from preventive strategies.